The Effect of Health Education on Breast Self-Examination (SADARI) on Knowledge, Attitudes, and Actions of Adolescent Girls - Andre Utama Saputra; Yulinda Ariyani; Suci Wahyuni; Arsi, Ranida; Nguyen, Thanh (Lentera Perawat, 2024)
Breast cancer not only occurs in developed countries but also in developing countries such as Indonesia. Breast cancer ranks 8th out of all cancers in Indonesia. Breast cancer is also a major concern, because it is the most common type of cancer affecting women. This study aims to determine the effect of breast self-examination health education on knowledge, attitudes, and actions of adolescent girls at SMK Kader Bangsa Palembang. This research method uses a quasi-experimental design with pretest posttest. The population was adolescents with menstrual cycles to 7-10 days with a total sample of 26 respondents who met the inclusion criteria. The test used was the Wilcoxon Sign Runk Test with p<0.05 using a computer. The results showed that health education on breast self-examination (SADARI) had an effect on knowledge p value (0.000<0.05), attitude p value (0.003)<(0.05), action p value (0.004)<(0.05). Conclusion There is an effect of health education on breast self-examination (SADARI) on knowledge, attitudes, and actions of adolescent girls at SMK Kader Bangsa Palembang. Suggestions are expected to schoolgirls can be made as a stewardship of SADARI techniques to detect early signs and symptoms of breast cancer.